Cabane à Sucre jako element dziedzictwa kulturowego Quebeku - Pilarek, Rafał (Zeszyty Wiejskie, 2014)
Cabane à sucre (Sugar house) is one of the most important elements of the traditional culinary culture of Quebec linked to maple syrup production in Eastern part of Canada. Every year in March, people gather in huts and houses to celebrate the beginning of the Maple Season. Among the traditional dishes, there are mainly Indian and French dishes. The most important element is the maple syrup which is served with every dish.